Soft-sensor model development for CHO growth/production, intracellular metabolite, and glycan predictions - Liang, George; Sha, Sha; Wang, Zhao; Liu, Huolong; Yoon, Seongkyu (Frontiers in Molecular Biosciences, 2024)
Therapeutic protein product quality is pivotal for efficacy, safety, and pharmacokinetics/pharmacodynamics. AssessingEfficaciously assessing product quality remains time-and resource-intensive. Online Process Analytical Technologies (PATs), encompassing realtime monitoring tools and soft-sensor models, are indispensable for understanding these process effects and real-time product quality. This research study evaluated three distinct modeling approaches for predicting CHO cell growth and production, intracellular metabolite concentrations (specificallymetabolites (extracellular, nucleotide sugar donors (NSD)),) and glycan profiles important for final product quality. These modeling approaches included mechanistic modeling):